A Sundanese Story of Hajj in the Colonial Period: Haji Hasan Mustapa’s Dangding on the Pilgrimage to Mecca - Rohmana, Jajang A. (Center for Research and Development of Religious Literature and Heritage, 2015)
The paper discusses a Sundanese story of hajj or pilgrimage to Mecca during the Dutch colonial period. It was expressed in the form of Sundanese metrical verse which was called dangding or guguritan. The author of the dangding was Haji Hasan Mustapa (1852-1930). He is one greatest Sundanese poets as he wrote more than 10 thousand cantos on Sufism from 1900-1902. He went to Mecca three times (1860-1862, 1869-1873, 1880-1885). One of his hajj stories was Kinanti Munggah Haji. Mustapa told about the hajj journey route, his experiences of suffering, and he also provided an interpretation of inner meaning of hajj according to the Sufi perspective. The paper uses an intertextual approach with an analysis of social history and Sufism. It shows that hajj in the colonial period was very difficult. In addition to the storm in the sea, the pilgrims found other difficulties in the Holy Land. However, Mustapa assumed that the meaning of hajj was not only the hajj ritual physically but also the inner-side of feeling (alaming rasa). Hajj will led to the true happiness. Beware if your hajj is just a physical matter. It can be nothing. The paper tries to confirm both van Dijk and Chambert-Loir’s works on other Sundanese stories of hajj such as Raden Panji Nagara, Moehammad-Hoesen, and R.A.A. Wiranatakoesoema. Mustapa’s interpretation of the mystical meaning of hajj shows his peculiarities as a sufi. His willingness to endure some difficulties in the journey is not just associated with his internal feeling in the sense of spiritual life, but also his satisfication to join in what Habermas called as a